Determination of whole genome sequence of human cytomegalovirus circulating in Japan and discovery of geographic genome structure in UL148 gene - Yuji Wada; Ken Ishioka; Tatsuo Suzutani (Virus Research)
Human cytomegalovirus (HCMV), a member of the Herpesviridae family, is prevalent worldwide. HCMV is generally asymptomatic but causes severe disease in immunocompromised patients or infants who are congenitally infected. Recent advances in sequencing technology have led to the rapid expansion of the HCMV genetic database, providing a comprehensive resource for studying viral genetics. Although genetic investigations have been vigorously performed in European countries, information on the whole-genome sequence of HCMV in the East Asian region remains limited. In this study, we determined whole-genome sequences of two clinical isolates of HCMV circulating in Japan. Partial genome sequences of 26 genes in UL/b' region were also identified using additional seven clinical isolates. Phylogenetic analysis of the UL148 gene revealed a characteristic genetic clade predominantly constructed from HCMV isolates from Japan and China, suggesting a geographic gene structure in the East Asian region. We consider that this research will contribute to expanding the genetic database of HCMV and unveiling novel genetic characteristics of HCMV in Asia.